Connectivity Benefits Most Woodland Invertebrate Species but Only in Landscapes With Low Woodland Cover - Charles A. Cunningham; Colin M. Beale; Diana E. Bowler; Michael J. O. Pocock; Robin Hutchinson; Piran C. L. White; Merryn Hunt; Lindsay Maskell; Jane K. Hill (Ecology Letters, 2025)
Connectivity is widely assumed to benefit biodiversity, but this has not been extensively quantified across multiple taxa and landscapes. Focusing on the UK, where woodland cover is low (13%), we analysed species occurrence records from citizen science for over 800 broadleaf woodland‐associated invertebrate species from 15 taxonomic groups in relation to woodland cover and connectivity. Overall, increased woodland connectivity positively affects broadleaf‐associated species occurrence (effect of connectivity across species, accounting for positive effect of broadleaf cover). The benefits of connectivity varied considerably by species: 39% of species showed a significant positive effect, while for 3% it was significantly negative. However, the interaction between cover and connectivity revealed that, overall, connectivity benefits are only found in low cover landscapes. Our findings emphasise potential biodiversity benefits from maximising connectivity when increasing woodland cover and highlight the importance of spatial targeting in restoration efforts, especially in landscapes with low woodland cover.

Development of soil health benchmarks for managed and semi-natural landscapes - Christopher J. Feeney; David A. Robinson; Aidan M. Keith; Audric Vigier; Laura Bentley; Richard P. Smith; Angus Garbutt; Lindsay C. Maskell; Lisa Norton; Claire M. Wood; B. Jack Cosby; Bridget A. Emmett (Science of The Total Environment, 2023)

Geomorphological and ecological change in a coastal foreland dune system, Sandscale haws, Cumbria, UK: the management challenges posed by climate change - Kenneth Pye; Simon J. Blott; Neil Forbes; Lindsay C. Maskell (Journal of Coastal Conservation, 2020)

Projecting trends in plant invasions in Europe under different scenarios of future land‐use change - Milan Chytrý; Jan Wild; Petr Pyšek; Vojtěch Jarošík; Nicolas Dendoncker; Isabelle Reginster; Joan Pino; Lindsay C. Maskell; Montserrat Vilà; Jan Pergl; Ingolf Kühn; Joachim H. Spangenberg; et al. (Global Ecology and Biogeography, 2012)
Aim Recent studies of plant invasions in habitat types across different climatic regions of Europe have made it possible to produce a European map of plant invasions. Parallel research led to the formulation of integrated scenarios of future socio‐economic development, which were used to create spatially explicit scenarios of European land‐use change for the 21st century. Here we integrate these two research lines and produce the first spatially explicit projections of plant invasions in Europe for the years 2020, 2050 and 2080. Location The European Union (except Bulgaria and Romania), Norway and Switzerland. Methods We used vegetation plots from southern, central and north‐western Europe to quantify mean levels of invasion by neophytes (post‐1500 alien plants) for forest, grassland, urban, arable and abandoned land. We projected these values on the land‐use scenarios for 2020, 2050 and 2080, and constructed maps of future plant invasions under three socio‐economic scenarios assuming: (1) deregulation and globalization, (2) continuation of current policies with standing regulations, and (3) a shift towards sustainable development. Results Under all scenarios an increase in the level of invasion was projected for north‐western and northern Europe, and under the first two scenarios a decrease for some agricultural areas of eastern Europe where abandonment of agricultural land is expected. A net increase in the level of invasion over Europe was projected under scenarios 2 and 3. Main conclusions The polarization between more and less invaded regions is likely to increase if future policies are oriented on economic deregulation, which may result in serious future problems in some areas of Europe. However, an implementation of sustainability policies would not automatically restrict the spread of alien plants. Therefore invasions require specific policy approaches beyond the more general ones, which are currently on the policy agenda and were tested in the scenarios.

Nitrogen deposition causes widespread loss of species richness in British habitats - LINDSAY C. MASKELL; SIMON M. SMART; JAMES M. BULLOCK; KEN THOMPSON; CARLY J. STEVENS (Global Change Biology, 2010)
We use national scale data to test the hypothesis that nitrogen (N) deposition is strongly negatively correlated with plant species richness in a wide range of ecosystem types. Vegetation plots from a national ecological surveillance programme were drawn from heathland, acid, calcareous and mesotrophic grassland habitats. Mean species number and mean plant traits were calculated for each plot and related to atmospheric N deposition. There was a significant reduction in species richness with N deposition in acid grassland and heathland even after fitting covarying factors. In acid grassland and heathland, evidence from trait changes suggested that acidification rather than increased fertility was responsible for species loss. In contrast, calcareous grassland showed evidence of eutrophication in response to increasing N deposition. Loss of species richness from chronic N deposition is apparent in infertile grasslands and heathland. Mechanisms associated with loss of species richness differ between habitats so mitigation of N deposition should be targeted to habitat type.